Peran Kualitas Layanan, Harga, dan Lokasi Usaha dalam Memuaskan Pelanggan: Kurnia Laundry Sleman - Dewi Larasati; Sofiati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In this era of intense competition, laundry businesses do their best to satisfy their customers so that they are not disappointed and meet their expectations. The urgency of this research aims to analyze the influence of service quality, price and business location on customer satisfaction. The population of this research is customers of Kurnia Laundry Sleman, using the Slovin method, the sample in the study was 100 people. The analysis method uses Multiple Linear Regression analysis. The research results found that service quality, price and business location together had a positive and significant effect on customer satisfaction. Partially, service quality has a positive and significant effect on customer satisfaction. Price does not have a significant effect on customer satisfaction. Location has a positive and significant effect on customer satisfaction. The contribution of the results of this research is that Kurnia Laundry Sleman should re-evaluate its pricing policy considering that price variables have no influence on customer satisfaction.